2002
DOI: 10.2337/diabetes.51.6.1938
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-Induced Apoptosis in Mouse Myocardium

Abstract: Diabetic cardiomyopathy is related directly to hyperglycemia. Cell death such as apoptosis plays a critical role in cardiac pathogenesis. Whether hyperglycemia induces myocardial apoptosis, leading to diabetic cardiomyopathy, remains unclear. We tested the hypothesis that apoptotic cell death occurs in the diabetic myocardium through mitochondrial cytochrome c-mediated caspase-3 activation pathway. Diabetic mice produced by streptozotocin and H9c2 cardiac myoblast cells exposed to high levels of glucose were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

41
406
2
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(467 citation statements)
references
References 44 publications
41
406
2
10
Order By: Relevance
“…One explanation proposed by some authors is that damaged cardiomyocytes are unable to synthesise ET-1 in response to Ang II stimulation [13,39,46]. For diabetes this explanation is excluded by our results.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…One explanation proposed by some authors is that damaged cardiomyocytes are unable to synthesise ET-1 in response to Ang II stimulation [13,39,46]. For diabetes this explanation is excluded by our results.…”
Section: Discussioncontrasting
confidence: 38%
“…The maximal decrease in bp was seen with combination treatment. The increase in systolic bp in diabetes mellitus could be related to the stimulatory effect of hyperglycaemia on the RAS [36,37,38] or generation of oxygen radical species reducing the availability of nitric oxide [39]. A normalisation of systemic bp in nonselective ET-1 blockade in diabetic rats is described [40].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it may also be structural-both apoptosis and necrosis have been identified in diabetic heart disease and myocyte cell death caused by either apoptosis or necrosis or both may be a major reason for the reduced myocardial contractility. Evidence in vivo has shown that hyperglycaemia directly induces apoptotic cell death and myocyte necrosis in the myocardium, triggered by reactive oxygen species derived from high levels of glucose [15]. Myocyte apoptosis and necrosis initiated by hyperglycaemia result in myocardial cell loss, which may impair the ability of the myocardium to develop force, accounting for reduced contractility.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies have shown that diabetes could be associated with enhanced susceptibility to apoptosis [5], we wanted to study in an experimental rat MI model, whether cardiomyocyte apoptosis is increased in diaDiabetic patients have about a two-fold increase in a risk of short-and long-term mortality after myocardial infarction (MI). Even after adjustment for the infarct betic compared to non-diabetic animals after MI, and whether it would relate to cardiac remodelling.…”
mentioning
confidence: 99%